Development of Socio-Religious Harmony Index Instrument for Malaysia - AHMAD YUSOFF, ATIFAH BINTI (2018)
This study contributes to understand the Malaysian socio-religious situation. Being a multi-religious country, Malaysia is not immune to contentious issues and incidents that challenge the relationship between different religious groups. Thus, it is crucial for the country to be conscious of its level of inter-religious relationship in order to maintain peaceful coexistence within the nation